Mendicidad e incidencia en el desarrollo integral de niñas y niños de la fundación ciudadanos en acción de la ciudad de Cuenca en la actualidad - Carrión Merino, Evelyn Tatiana (2025)
Child begging is a social problem of great relevance that affects the integral development of girls and boys, especially in contexts of social vulnerability. This study focuses on the incidence of begging on the development of minors belonging to the Fundación Ciudadanos en Acción in the city of Cuenca, identifying the factors that perpetuate this situation and the repercussions on their physical, emotional and social well-being. The main objective is to analyse the impact of begging on the integral development of these children and to propose intervention strategies that contribute to improving their quality of life. A mixed approach methodology was used, combining quantitative analysis through Likert-type surveys applied to children, and qualitative analysis through interviews with foundation staff to understand the social and family dynamics that favour begging. As a result, the main factors that influence child begging were identified, which are economic precariousness, family disintegration and lack of access to services such as education and health, as well as the fact that most of the children involved in begging come from families in extremely vulnerable situations. In addition, the results show the importance of strengthening family and community support networks to reduce the impact of begging on children's overall development. Fifty-eight per cent of children engage in begging in order to collaborate economically, and 61 per cent face constant insufficiency of resources. In addition, 53% of children report that they are influenced by their parents to ask for money. In terms of overall development, 55% of the children do not have the necessary resources to study, which limits their academic performance. Despite a positive perception of emotional support at home (68%), 79% of children do not perceive this as a comprehensive protective factor. It was concluded that child begging is related to structural factors such as extreme poverty, family abandonment and societal dynamics. A proposal for social intervention based on educational, emotional and economic strategies was put forward, which sought to prevent this problem by promoting an environment of integral development for the children affected. Recommendations include strengthening interdisciplinary programmes as well as implementing policies of access to basic resources and developing intervention plans in collaboration with other institutions